2022
DOI: 10.1167/jov.22.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Cortical distance unifies the extent of parafoveal contour interactions

Abstract: It is well known that crowding, the disruptive influence of flanking items on identification of targets, is the primary limiting factor to object identification in the periphery, while limits in the fovea are more determined by the ability to resolve individual items. Whether this is a dichotomous or merely a quantitative difference, and the transition between these two regimes, has remained unexplained. Here, using an adaptive optics system for optimal control of optical and stimulus factors, we measured thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…Visual crowding is a perceptual phenomenon that impairs the recognition of targets when surrounded by flankers ( Balas, Nakano, & Rosenholtz, 2009 ; Bouma, 1970 ; Greenwood, Szinte, Sayim, & Cavanagh, 2017 ; Harrison & Bex, 2015 ; He, Cavanagh, & Intriligator, 1996 ; Kwon & Liu, 2019 ; Parkes, Lund, Angelucci, Solomon, & Morgan, 2001 ; Pelli, & Tillman, 2008 ; Pelli et al, 2004 ; Toet & Levi, 1992 ; Wallis & Bex, 2011 ; Whitney & Levi, 2011 ). Although crowding is typically associated with the peripheral vision, emerging evidence has pointed to the presence of measurable crowding in the foveal vision ( Coates et al, 2018 ; Coates et al, 2022 ; Danilova & Bondarko, 2007 ; Flom et al, 1963 ; Lev et al, 2014 ; Pelli et al, 2016 ; Siderov et al, 2013 ; Strasburger et al, 1991 ; Toet & Levi, 1992 ). Studies have used a variety of tasks, targets (different types and sizes), and flankers (different numbers and types of flankers), under limited or unlimited stimulus durations to measure the spatial extent of foveal crowding and reported a range of approximately 0.0125 degrees to 0.1 degrees for the extent of foveal crowding for normal healthy vision ( Coates et al, 2018 ; Danilova & Bondarko, 2007 ; Flom et al, 1963 ; Marten-Ellis & Bedell, 2021 ; Pelli et al, 2016 ; Siderov et al, 2013 ; Toet & Levi, 1992 ; Wolford & Chambers, 1984 ) as summarized in Figure 2 A(i).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual crowding is a perceptual phenomenon that impairs the recognition of targets when surrounded by flankers ( Balas, Nakano, & Rosenholtz, 2009 ; Bouma, 1970 ; Greenwood, Szinte, Sayim, & Cavanagh, 2017 ; Harrison & Bex, 2015 ; He, Cavanagh, & Intriligator, 1996 ; Kwon & Liu, 2019 ; Parkes, Lund, Angelucci, Solomon, & Morgan, 2001 ; Pelli, & Tillman, 2008 ; Pelli et al, 2004 ; Toet & Levi, 1992 ; Wallis & Bex, 2011 ; Whitney & Levi, 2011 ). Although crowding is typically associated with the peripheral vision, emerging evidence has pointed to the presence of measurable crowding in the foveal vision ( Coates et al, 2018 ; Coates et al, 2022 ; Danilova & Bondarko, 2007 ; Flom et al, 1963 ; Lev et al, 2014 ; Pelli et al, 2016 ; Siderov et al, 2013 ; Strasburger et al, 1991 ; Toet & Levi, 1992 ). Studies have used a variety of tasks, targets (different types and sizes), and flankers (different numbers and types of flankers), under limited or unlimited stimulus durations to measure the spatial extent of foveal crowding and reported a range of approximately 0.0125 degrees to 0.1 degrees for the extent of foveal crowding for normal healthy vision ( Coates et al, 2018 ; Danilova & Bondarko, 2007 ; Flom et al, 1963 ; Marten-Ellis & Bedell, 2021 ; Pelli et al, 2016 ; Siderov et al, 2013 ; Toet & Levi, 1992 ; Wolford & Chambers, 1984 ) as summarized in Figure 2 A(i).…”
Section: Discussionmentioning
confidence: 99%
“…the minimum spacing between a target and flankers required for reliable target identification), increases with increasing retinal eccentricity ( Bouma, 1970 ; Pelli et al, 2004 ; Whitney & Levi, 2011 ). Thus, visual crowding is known to be more pronounced in the peripheral vision, whereas little crowding exists in the foveal vision ( Coates, Jiang, Levi, & Sabesan, 2022 ; Coates, Levi, Touch, & Sabesan, 2018 ; Danilova & Bondarko, 2007 ; Flom, Weymouth, & Kahneman, 1963 ; Lev, Yehezkel, & Polat, 2014 ; Levi, Klein, & Hariharan, 2002 ; Pelli, Waugh, Martelli, Crutch, Primativo, Yong, Rhodes, Yee, Wu, Famira, & Yiltiz, 2016 ; Siderov, Waugh, & Bedell, 2013 ; Strasburger, Harvey, & Rentschler, 1991 ; Toet & Levi, 1992 ). However, some conditions, such as amblyopia, exhibit significantly increased foveal crowding ( Bonneh, Sagi, & Polat, 2007 ; Flom et al, 1963 ; Hariharan, Levi, & Klein, 2005 ) compared to what is expected from normal vision.…”
Section: Introductionmentioning
confidence: 99%
“…Given the prominence of cortical distance as an explanation of variations in crowding (Levi, Klein, & Aitsebaomo, 1985; Motter & Simoni, 2007; Pelli, 2008; Coates et al, 2022), we first sought to dissociate physical from cortical distance using the division of the left and right sides of the visual field, which project to the right and left hemispheres, respectively (Sereno et al, 1995; Wandell, Dumoulin, & Brewer, 2007). Liu et al (2009) noted that this hemispheric separation of the hemifields would cause a contralateral flanker on the opposite side of the vertical meridian to the target to be more distant cortically than an ipsilateral flanker on the same side of the meridian, despite both having matched physical distance.…”
Section: Resultsmentioning
confidence: 99%
“…Because retinotopic visual areas show cortical magnification, with an expanded representation of the visual field around the fovea relative to the periphery (Daniel & Whitteridge, 1961; Wandell, Dumoulin, & Brewer, 2007; Strasburger, 2020), target and flanker elements with a fixed distance in the visual field would shift closer together cortically as they moved into the periphery. The increase in crowded performance decrements with eccentricity has been attributed to this decrease in cortical distance (Levi, Klein, & Aitsebaomo, 1985; Motter & Simoni, 2007; Pelli, 2008; Coates, Jiang, Levi, & Sabesan, 2022). Variations in the effect of crowding on appearance have also been linked with cortical distance, with the predominance of repulsion at parafoveal eccentricities attributed to the larger cortical distance between elements compared to the periphery, where the decrease in cortical distance promotes assimilation (Mareschal, Morgan, & Solomon, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies using vernier targets showed similar effects in the fovea and in the periphery (e.g., Sayim, Westheimer, & Herzog, 2010 ; Manassi, Sayim, & Herzog, 2012 ), results for letter targets are less clear. Coates, Jiang, Levi, and Sabesan (2022) investigated crowding with tumbling Es flanked by bars at several eccentricities in the parafovea. Using adaptive optics, they found that the different results at different eccentricities could be well-summarized by a single function, unifying the varying results.…”
mentioning
confidence: 99%